(untitled) (Research, Society and Development, 2020)
Objectives: The objective of this work was to evaluate the in vitro anti-mycotoxin capacity of two commercial probiotics consisting of spores of Bacillus spp - A1 and A2 and of the microalgae Chaetoceros gracilis - A3 used to feed Litopenaeus vannamei for aflatoxin B1 (AFB1) and ochratoxin A (OTA). The amount of probiotic was calculated for 10 L of water. The amount of Chaetoceros gracilis microalgae was calculated according to the amount used in the farms (12 x 104 cells / mL). A group with five microtubes of each probiotic with pH 2.0 and another group with pH 6.0 was prepared using phosphate buffered saline (PBS) in duplicate to simulate the stomach and intestinal pH of the shrimp, respectively. The concentrations of probiotics used were 0.0%; 25%; 50%; 75% and 100% (0.0025 g; 0.005 g; 0.0075 g; 0.010 g) in each tube. The same concentration of microalgae was used. The concentration of mycotoxins was 1.000 ng / mL. The anti-mycotoxin activity of A1, A2 and A3 for OTA and AFB1 were performed by high performance liquid chromatography. There was a difference in the anti-mycotoxin capacity between the probiotics tested for OTA and AFB1 with greater efficiency of A2. A3 did not show anti-mycotoxin activity. In A1 and A2 the adsorption of OTA and AFB1 started from the 25% concentration. Half of the OTA (513 ng / mL) was adsorbed using A2 (concentrations ≥ 50%) at pH 2.0 and A1 (concentrations ≥75%) at the same pH (400 ng / mL). For AFB1 the greatest adsorption occurred in A2 (concentrations ≥75%) at pH 2.0 (643 ng / mL) and pH 6.0 (672 ng / mL). The greatest anti-mycotoxin effect of A1 only occurred (concentrations ≥ 50%) at pH 2.0 (481 ng / mL) and 25% at pH 6.0 (592 ng / mL). Probiotics made up of spores of Bacillus spp have anti-mycotoxin capacity in vitro for AFB1 and OTA and the microalgae Chaetoceros gracilis did not show this capacity.